Harmonisasi Antar Etnis dan Implikasinya terhadap Ketahanan Wilayah di Kalimantan Barat Pada Era Society 5.0 - Muhammad Hendri Nuryadi; Pipit Widiatmaka (Universitas Gadjah Mada, 2022)
ABSTRACT This study aimed to found out the challenges of ethnic diversity in West Kalimantan in the era of society 5.0; found out strategies for implementing tolerance values in the era of society 5 in West Kalimantan; and found out the implications of regional resilience in West Kalimantan.This study used a qualitative approach and used a descriptive method. The data collection techniques used were in-depth interviews and random sampling techniques, and) literature review (journal articles, proceedings articles, online news accessed on the internet, magazines and books). The data analysis technique in this study had several stages, namely collecting data, condensing data, presenting data, and conclusion.The results of the study showed that the era of society 5.0 was a challenge for ethnic diversity in West Kalimantan, due to the rapid flow of information (hoax) that developed on social media. The response was to implemented the values of tolerance in the life of the nation and state (both in the real and virtual worlds). People in West Kalimantan must be able to realized that it was very important to established a harmonious life for the sake of unity and integrity. The attitudes that must be applied were working together and not looking at differences, realizing that everyone had the same rights, respecting and respecting each other, and accepting other people's opinions, even though they had different opinions. This had implications for strong regional resilience in West Kalimantan, because it affected the existence of ideology, political stability, economic growth, harmonious socio-cultural life, good defense and security.